The impact of fiscal decentralization on the composition of public expenditure in Chinese prefecture-level cities: does fiscal transparency matter? - Liu, Cong; Abd Ghani, Judhiana; Thinng, Wency Bui Kher (Asian Economic and Social Society, 2025)
This research examines how fiscal decentralization influences the composition of public spending in Chinese prefecture-level cities, with a focus on the moderating role of fiscal transparency. We analyzed data from 283 Chinese cities from 2013 to 2022 using a special statistical model that accounts for changes over time and other factors. The findings indicate that fiscal decentralization negatively affects the share of public expenditure allocated to science and technology, education, and social security and employment. However, as fiscal transparency increases, these negative effects diminish, with the impact on science and technology spending becoming significantly positive at higher levels of transparency. In contrast, the marginal effects on healthcare expenditure are initially positive but insignificant, and they become significantly negative once transparency exceeds a certain threshold. These results underscore the critical moderating role of fiscal transparency in local governments' expenditure decisions in response to fiscal decentralization. The findings offer valuable insights for policymakers on how enhancing fiscal transparency can mitigate the negative impacts of fiscal decentralization and promote more efficient public expenditure allocation.